The Liquidation of Government Debt - Reinhart, Carmen; Sbrancia, M. Belen (Washington, D.C. : International Monetary Fund, 2015)
High public debt often produces the drama of default and restructuring. But debt is also reduced through financial repression, a tax on bondholders and savers via negative or belowmarket real interest rates. After WWII, capital controls and regulatory restrictions created a captive audience for government debt, limiting tax-base erosion. Financial repression is most successful in liquidating debt when accompanied by inflation. For the advanced economies, real interest rates were negative 1\2 of the time during 1945-1980. Average annual interest expense savings for a 12-country sample range from about 1 to 5 percent of GDP for the full 1945-1980 period. We suggest that, once again, financial repression may be part of the toolkit deployed to cope with the most recent surge in public debt in advanced economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet